Body composition and maximal exercise capacity after heart transplantation. (2nd December 2021) - Regamey, Julien; Monney, Pierre; Yerly, Patrick; Favre, Lucie; Kirsch, Matthias; Tozzi, Piergiorgio; Lamy, Olivier; Hullin, Roger
Abstract: Aims: Maximal exercise capacity as measured by peak oxygen consumption (pVO2 ) in cardiopulmonary exercise testing (CPET) of heart transplant recipients (HTR) is limited to a 50–70% level of healthy age‐matched controls. This study investigated the relationship between body composition and pVO2 during the first decade post‐transplant. Methods and results: Body composition was determined by dual‐energy X‐ray absorptiometry (DXA) and pVO2 by CPET in 48 HTR ( n = 38 males; mean age 51 ± 12 years). A total of 95 assessments were acquired 1–9 years post‐transplant, and the results of four consecutive periods were compared [Period 1: 1–2 years ( n = 25); 2: 3–4 years ( n = 23); 3: 5–6 years ( n = 23); 4: 7–9 years ( n = 24)]. Linear regression analysis analysed the correlation between pVO2 and pairs of appendicular lean mass (ALM) and fat mass (FM). The relation between ALM and daily dose of calcineurin inhibitor (CNI) was explored using partial correlation controlling for age, gender, and height. pVO2 increased from 0.98 (0.34) to 1.35 (0.35) L/min ( P < 0.01) between Periods 1 and 4 corresponding to 54.5–63.3% of predicted value. Peak heart rate (HR) raised from 115 ± 19 to 131 ± 23 b.p.m. ( P = 0.05), and anaerobic threshold (AT = VO2 achieved at AT) increased from 0.57 (0.18) to 0.83 (0.35) L/min ( P < 0.01) between Periods 1 and 3. Median FM normalized to height 2 (FMI) always remained elevated (>8.8 kg/m 2 ). ALM normalized to body mass index increased from 0.690 (0.188) to 0.848 (0.204) m 2 ( P = 0.02) between Periods 1 and 4, explaining 45% of the variance of pVO2 ( R 2 = 0.455; P < 0.001). Eighty‐one per cent of the variance of pVO2 ( R 2 = 0.817; P < 0.001) in multiple regression was explained by AT ( β = 0.488), ALM ( β = 0.396), peak HR ( β = 0.366), and FMI ( β = −0.181). ALM was negatively correlated with daily CNI dose (partial R = −0.258; P = 0.01). Conclusions: After heart transplantation, the beneficial effect of peripheral skeletal muscle gain on pVO2 is opposed by increased FM. Our findings support lifestyle efforts to fight adiposity and CNI dose reduction in the chronic stable phase to favour positive adaptation of peripheral muscle mass.